Lanternas flutuantes : praticas artísticas de participação comunitária com habitantes das ilhas no bairro Arquipélagos em Porto Alegre, na era do Antropoceno - Baptista, Ricardo Alfonso Moreno (2018)
This research project is focused on the considerations of the separated people from art systems in artistic process. The inhabitants of the Arquipélago neighborhood located in the city of Porto Alegre, Brazil were addressed with PAPC (Artistic Practices of Community Participation) between 2014 and 2017. The argumentation constructed through this thesis is about PAPC established as work strategy and a community organization allowing collectively constructions, specifically, an artwork that involves all the contributions, knowledge and effort of the different groups and social networks of the community. Therefore, Colombian and Mexican PAPC and PAPCol (Artistic Practices of Community Collaboration) experiences, between 1978 and 2014, were presented. The Anthropocene notion is also considered, due to the visible and palpable actual climate change effects on the community contexts, allowing us to question the social function of art facing this contextual reality. The creation laboratories are described, and were carried out in three different educational centers located in La Pintada Island, which resulted in two events called “Noite das Lanternas Flutuantes” on December 16th of 2015 and “Vagalumes no Jacuí” on June 29th of 2016, and finally a third event with the community called “Mboitatá no río Jacuí” on December 18th of 2016 The methodological strategy carried out during the research development, consisted on a series of activities based on horizontal dialogical relationships between the artist and the community, allowing knowledge exchange and collective synergies through which an eventhappening was created as an artwork. The fieldwork evidenced the need for the artist to develop an availability condition to know about the different historical, social, economic, political, cultural and environmental aspects characteristic of the community, through which the artist serves as facilitator on the development of network tissue and organizational processes which supported the realization of the event. In conclusion, the island community to whom the work was carried out, was able to consolidate interpersonal and group interaction relationships which allow them to establish cooperation networks, with a significant level of autonomy, to achieve the proposed objective and the availability to project action towards the future.